Overview Of Primipara Mother's Knowledge About ASI Storage In TPMB Nanik Kediri District - Wardhani, Ratih Kusuma; Mardiana , Heppy Rina Mardiana; Wulandari, Ratna Feti (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Breastfeeding is one of the contributions to the health, growth and development of newborns, infants and children. Based on WHO data, coverage of exclusive breastfeeding will decrease in 2022 compared to 2021. This condition is caused by a lack of knowledge about good and correct management of breast milk, especially breast milk storage. The aim of this research is to determine the description of Primiparous Mothers' knowledge about breast milk storage. Method: The research design used a descriptive cross-sectional approach, the research sample was 20 primiparous mothers in the TPMB Nanik Tulungrejo Village, Pare District, Kediri Regency. The variable studied was knowledge about breast milk storage. Data was collected using a questionnaire and analyzed using frequency distribution tables and cross tabulation. Result: The research results obtained from 20 respondents and showed that the majority were well-informed mothers (45%), exclusively breastfeeding mothers (65%). The results of the overall data analysis can be concluded that there is a picture of primiparous mothers' knowledge about storing breast milk. Conclusion: Breastfeeding mothers need support from family and society so they need information according to their level of education and knowledge, or to facilitate understanding of the importance of storing breast milk correctly and appropriately.